2012
DOI: 10.3391/ai.2012.7.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and zooplankton-predation impact of the indigenous scyphozoan Aurelia aurita and the invasive ctenophore Mnemiopsis leidyi in Limfjorden (Denmark)

Abstract: The invasive ctenophore, Mnemiopsis leidyi, which had its first mass occurrence in Limfjorden (Denmark) . During that period, copepods and other mesozooplankton organisms were virtually absent while ciliates were a substantial part of the zooplankton biomass. In "pre-Mnemiopsis years", there seems to have been large variability in the grazing impact on zooplankton depending on the seasonal abundance of A. aurita. With the addition of the second carnivore M. leidyi, however, additional predation pressure caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…13 Riisgård et al, 2012), compete with other zooplanktivorous species, including fishes (Purcell & Arai, 2001) and have a direct impact on fish stocks by feeding on fish larvae and eggs (Purcell, 1985). In the present study, the majority of B. virginica medusae did not have zooplankton prey in the guts (89.4% vacuity index).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…13 Riisgård et al, 2012), compete with other zooplanktivorous species, including fishes (Purcell & Arai, 2001) and have a direct impact on fish stocks by feeding on fish larvae and eggs (Purcell, 1985). In the present study, the majority of B. virginica medusae did not have zooplankton prey in the guts (89.4% vacuity index).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…in coastal areas (Purcell et al, 2001(Purcell et al, , 2007. Nowadays, it is extensively accepted that gelatinous zooplankton are key components of marine food web both as major predators of metazooplankton (Purcell, 1997;Riisgard et al, 2011) and as prey of apex predators, such as tuna, billfish, sunfish, and sea turtles (Arai, 2005;Cardona et al, 2012). In addition, increasing evidence has shown that gelatinous zooplankton influence the microbial food web, through direct and indirect effects, besides regulating the marine biogeochemical fluxes (Pitt et al, 2005;Turk et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, in the Black Sea M. leidyi has caused rapid community shifts and depletion of fish stocks (Oguz and Gilbert, 2007). More recently, their proliferation in the North and Baltic seas has generated substantial research into the potential top-down and competitive structuring forces in pelagic food webs (Hosia and Titelman, 2011;Javidpour et al, 2009;Kellnreitner et al, 2013; but see Hamer, Malzahn, and Boersma, 2011;Jaspers et al, 2011) and species interactions between M. leidyi and other gelatinous zooplankton species (Riisgård, Barth-Jensen, and Madsen., 2010;Riisgård et al, 2012). Within its native range, M. leidyi has always played an important role in pelagic food webs (Deason and Smayda, 1982;Mountford, 1980;Nelson, 1925), but with increasing anthropogenic stresses related to eutrophication and overfishing, their relative abundance and influence on communities has led to broader structuring effects in coastal communities (Breitburg et al, 2010;McNamara, Lonsdale, and Cerrato, 2010;.…”
Section: Introductionmentioning
confidence: 99%